The effects of ozone therapy on postoperative adhesions and ovarian functions: An experimental study - Deniz, Rulin; Baykuş, Yakup; Uzuner, Muhammet Bora; Adalı, Yasemen (Journal of Surgery and Medicine, 2020)
Aim: Numerous methods are used to prevent the development of postoperative adhesion formation. There are few studies on the effects of ozone therapy on postoperative intraabdominal adhesions and ovarian functions. This study aimed to investigate the effects of ozone treatment on postoperative intraabdominal adhesions and ovarian roles in rats. Methods: Twenty female Wistar albino rats were randomly allocated into two groups as laparotomy (Group 1, n: 10) and laparotomy + intraperitoneal ozone (Group 2, n: 10). After laparotomy, parietal peritoneum, uterus and adnexal surfaces were scraped in both groups. Follicle-stimulating hormone (FSH), Estradiol (E2), Lactate Dehydrogenase (LDH), Urea, and Creatinine levels were measured, and histopathological evaluation was performed. Both groups were compared concerning histopathological and biochemical findings. Results: In the ozone-treated group, antioxidant levels (P=0.012) were significantly higher, and E2 levels (P=0.005) were substantially lower than the control group. There was no statistically significant difference between the two groups regarding FSH, Urea, Creatinine, and LDH (P=0.12, P=0.72, P=0.45, and P=0.79, respectively). Histopathologically, postoperative intraabdominal adhesion rates between the two groups were statistically similar. Conclusion: Although there was no statistically significant difference, ozone therapy had a decreasing effect on severe fibrosis and congestion rates. Although there was no difference in FSH, low levels of E2 in Group 2 suggest that ozone treatment may have a protective effect on the ovaries. However, further studies are needed concerning adhesion formation and the impact on ovarian functions.